bahasa inggis - Marbun, Krisnayanti; Khoiri, M. (SCIENTIA JOURNAL, 2023)
Purchasing decisions are thoughts where individuals evaluate various choices and decide on a product from among the many choices. Purchasing decisions are the stage in the decision-making process where consumers actually buy. Decision making is an individual activity that is directly involved in the process of purchasing goods offered by the company. Purchasing decision is a process of making a purchase decision which includes determining what to buy or not to buy and the decision is obtained from previous activities. The purpose of this study was to determine the effect of brand image on purchasing decisions, the effect of promotion on purchasing decisions, the effect of trust on purchasing decisions and the effect of brand image, promotion and trust on purchasing decisions for garnier facial cleansers in BatamCity. This study uses quantitative research methods with multiple linear regression analysis. The results showed that there is a positive and significant influence between brand image on purchasing decisions, there is a positive and significant influence between promotions on purchasing decisions, there is a positive and significant influence between trust on purchasing decisions and there is a positive and significant influence between brand image, promotion and trust on purchasing decisions for garnier facial cleansers in Batam City. Keywords: Brand Image, Promotion, Trust, Purchasing Decisions